ASSESSING THE IMPACT OF GREEN MARKETING ON FMCG SALES IN ERNAKULUM (International Journal of Food and Nutritional Sciences, 2024)
Green marketing has gained prominence as consumers become increasingly conscious of environmental sustainability. This study assesses the impact of green marketing strategies on the sales performance of Fast-Moving Consumer Goods (FMCG) in Ernakulum. The research examines how eco-friendly packaging, sustainable sourcing, green branding, and consumer awareness influence purchasing decisions and overall sales growth. Through a mixed-method approach, data is collected from FMCG companies and consumers in Ernakulum to analyze the effectiveness of green marketing initiatives. The findings highlight that consumers are more inclined to purchase eco-friendly products when they perceive them as beneficial to the environment and their well-being. Additionally, companies that adopt green marketing strategies experience improved brand loyalty and market competitiveness. However, challenges such as higher production costs and consumer skepticism regarding green claims are also explored. The study contributes to understanding the role of green marketing in shaping consumer behavior and provides insights for FMCG companies to enhance their sustainability-driven marketing efforts.